PERSISTENCE OF VIRAL HEPATITIS A AND B IN AN ISOLATED CAUCASIAN POPULATION - SKINHøJ, P.; MATHIESEN, L. R.; COHN, J. (Oxford University Press, 1980)
The persistence of viral hepatitis A (HAV) and hepatitis B (HBV) in the Faroe Islands, a Caucasian, high sanitary standard, isolated area, was studied by means of notified clinical cases of hepatitis and by specific antibody testing of population samples. Large epidemics of hepatitis occurred on the Faroe Islands in 1928–1930 and 1955–1958, although sporadic cases have been continuously recorded. Presence of antibody to HAV (anti-HAV) was confined to age groups exposed to the epidemics, while antibody to HBV surface antigen (anti-HBs) was demonstrated in all age groups, including children. This study provides further evidence for the concept of HAV as a self-limited infection, unable to maintain itself by chronic virus carriers. HBV, by contrast, again is shown to survive even in small populations with high sanitary conditions and to have no recognizable risk factors.